A process for preparing high-compaction lithium iron phosphate based on ferrous phosphate precursor

CN122940137APending Publication Date: 2026-10-20GUIZHOU PHOSPHATE KAIRUI TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611412327.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种基于磷酸亚铁前驱体制备高压实磷酸铁锂的工艺,该工艺能够解决现有技术中二次烧结导致级配失效、双前驱体工艺复杂、粒度控制缺乏量化手段、碳包覆工艺繁琐以及依赖特殊添加剂等多重技术问题问题

Benefits of technology

(一)避免二次烧结导致的级配失效,精准保持预设粒度峰形

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application relates to the field of lithium iron phosphate preparation technology, specifically disclosing a process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor, comprising: mixing ferrous phosphate precursor, lithium source, carbon source, titanium source, dispersant and solvent, and performing sand milling of different particle sizes, controlling the D50 of the first sand milling slurry to be 0.2~0.4μm and the D50 of the second sand milling slurry to be 0.8~1.5μm; the two slurries are respectively spray granulated, segmented sintered and crushed and classified to obtain a first powder with a D50 of 0.6~1.2μm and a Span of 2.5~4.5 and a second powder with a D50 of 2.5~4.5μm and a Span of 2.0~3.5; the two powders are mixed by matching the particle size peak shape so that the particle size distribution curve of the mixed powder exhibits at least three peaks, thus obtaining the finished product. This invention achieves multi-level close packing by independently controlling the grinding particle size and sintering process, allowing particles of different sizes to crystallize under optimal conditions. Combined with quantitative peak shape matching, this results in a compaction density ≥2.50 g / cm³. 3 It has a specific capacity of ≥157mAh / g at 0.1C and a retention rate of ≥95% after 500 cycles at 1C. The process is controllable and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium iron phosphate preparation technology, specifically a process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor. Background Technology

[0002] Lithium iron phosphate (LFP) possesses outstanding advantages such as stable operating voltage, high safety, long cycle life, wide availability of raw materials, and environmental friendliness, making it one of the most widely used cathode materials in the fields of power batteries and energy storage batteries. However, limited by its olivine crystal structure, LFP exhibits low intrinsic electronic conductivity, a small lithium-ion diffusion coefficient, and a relatively low true density compared to other cathode materials; the compacted density of powder obtained through conventional processes is typically only 2.2–2.5 g / cm³. 3 This has limited further improvements in the volumetric energy density of battery cells. With the increasing demands for driving range and battery pack space utilization in new energy vehicles, how to significantly improve the compaction density of lithium iron phosphate while maintaining electrochemical performance has become a key issue that urgently needs to be addressed in this field.

[0003] Studies have shown that a gradation strategy employing particles of different sizes to fill each other is an effective way to improve powder bulk density and thus compaction density. Various implementation methods have been developed around this strategy, but each has its inherent shortcomings. One type of technical solution uses raw materials or intermediates of different particle sizes for gradation. For example, patent CN120887394A uses iron source precursors of different particle sizes, and patent CN121085239A uses differentiated doping of lithium iron phosphate particles of different sizes before compounding. In this type of solution, the crystallization quality of different components is difficult to optimize independently in a unified subsequent process, and particle agglomeration during sintering can easily cause deviations from the preset gradation ratio. Another type of technical solution uses separate preparation of coarse and fine particles, followed by a second sintering to create a composite product. For example, patent CN120039852A first uses ferrous phosphate and iron phosphate as precursors, respectively, and after grinding, spray drying, and a first sintering, coarse and fine lithium iron phosphate particles are obtained. These particles are then mixed and subjected to a second spray drying and a second sintering. The main drawbacks of this type of scheme are: secondary high-temperature sintering causes recrystallization and intergranular agglomeration of the separately crystallized primary particles, easily disrupting the pre-designed bimodal gradation structure, and posing a risk of the product particle size distribution narrowing back to a single distribution; the two particle grades use precursors from two different sources, ferrous phosphate and ferric phosphate, whose reactivity and sintering behavior are inconsistent, requiring matching process windows separately, thus improving process compatibility; furthermore, the carbon source needs to be added multiple times before the primary sintering and during the secondary mixing, making precise control of carbon content difficult. Another type of technical scheme achieves particle size differentiation by adjusting spray drying process parameters. For example, CN121225563A uses ferrous phosphate as a precursor, promoting large-particle crystal growth by adjusting the feed rate and spray pressure of the spray dryer. In this type of scheme, the spray parameters are strongly coupled with the slurry properties, resulting in a limited adjustable particle size window, and batch-to-batch consistency needs further improvement in large-scale production; moreover, particles of different sizes still undergo the same sintering regime, making it difficult to crystallize independently under their respective optimal conditions. In addition, existing literature has proposed quantitative requirements for multimodal particle size distribution from the product perspective. For example, CN120246971A discloses the structural characteristics of lithium iron phosphate powder particle size distribution curves containing three particle size peaks. However, such solutions mainly focus on describing the particle size characteristics of the product and have not yet disclosed how to actively and stably achieve this multi-peak distribution through process path design. Based on this, it is still difficult for those skilled in the art to achieve "controllable peak shape" industrial production.

[0004] In summary, the existing technology has not yet established a high-pressure lithium iron phosphate preparation process that can achieve active particle size design in the precursor stage, optimize the crystallization quality of each particle grade separately, and finally achieve particle size peak shape matching by quantitative means. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursors. This process can solve multiple technical problems in existing technologies, such as gradation failure caused by secondary sintering, complexity of dual precursor processes, lack of quantitative means for particle size control, cumbersome carbon coating processes, and reliance on special additives.

[0006] To address the above technical problems, in a first aspect, the present invention provides a process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor, comprising the following steps: S1. Preparation of the first powder: Ferrous phosphate precursor, lithium source, carbon source, dispersant, titanium source and solvent are mixed to obtain a first mixed slurry; then the first mixed slurry is sand-milled to obtain a first sand-milled slurry; the first sand-milled slurry is spray-dried and granulated, and the resulting material is then subjected to segmented sintering, crushing and classification to obtain the first powder; wherein, the particle size D50 of the first sand-milled slurry is 0.2~0.4μm; the D50 of the first powder is 0.6~1.2μm, and the particle size distribution span is 2.5~4.5; the segmented sintering is carried out in two stages under a protective atmosphere, the first stage sintering temperature is 300~500℃, and the second stage sintering temperature is 650~800℃; S2. Preparation of the second powder: Ferrous phosphate precursor, lithium source, carbon source, dispersant, titanium source, and solvent are mixed to obtain a second mixed slurry; then the second mixed slurry is milled to obtain a second milled slurry; the second milled slurry is spray-dried and granulated, and the resulting material is then subjected to segmented sintering, pulverization, and classification to obtain the second powder; wherein, the particle size D50 of the second milled slurry is 0.8~1.5μm; the D50 of the second powder is 2.5~4.5μm, and the particle size distribution span is 2.0~3.5; the segmented sintering is carried out in two stages under a protective atmosphere, with the first stage sintering temperature at 300~500℃ and the second stage sintering temperature at 650~800℃; S3. Peak shape matching: The first powder and the second powder are mixed so that the particle size distribution curve of the mixed powder exhibits at least three peaks, thereby obtaining high-pressure lithium iron phosphate material.

[0007] Furthermore, in S1 and S2, the sand grinding is carried out using a sand mill, and the grinding time is 0.5 to 3 hours.

[0008] Furthermore, in S1 and S2, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate; the carbon source is selected from at least one of glucose, sucrose, polyethylene glycol, citric acid, and carbon nanotubes; the titanium source is selected from at least one of titanium dioxide, titanium oxysulfate, chelated titanium, and metatitanic acid; the solvent is deionized water; and the dispersant is selected from one or more of ammonium polyacrylate, polyethylene glycol, and polyvinylpyrrolidone.

[0009] Furthermore, in S1 and S2, the amount of dispersant added is 0.1% to 1.0% of the mass of the ferrous phosphate precursor in each step; the molar ratio of lithium to iron in the lithium source and the ferrous phosphate precursor in each step is 1.01:1 to 1.05:1; the amount of titanium source added in each step is 0.4% to 1.5% of the mass of the ferrous phosphate precursor in each step; and the amount of carbon source added in each step is such that the mass percentage of carbon in the powders prepared in S1 and S2 is 1.0% to 2.0%.

[0010] Furthermore, in S1 and S2, the first stage sintering is followed by heat preservation for 2 to 6 hours, and the second stage sintering is followed by heat preservation for 6 to 12 hours; in each step, the pulverization is mechanical pulverization and / or airflow pulverization, and the grading is performed using an airflow classifier or a vibrating screen.

[0011] Furthermore, the protective atmosphere is nitrogen or argon.

[0012] Furthermore, in S3, the mass ratio of the first powder to the second powder is 30:70 to 70:30.

[0013] Secondly, a lithium iron phosphate cathode material prepared by the process described in the first aspect of the present invention is provided, wherein the compaction density of the lithium iron phosphate cathode material is ≥2.50 g / cm³. 3 0.1C specific capacity ≥157mAh / g, 1C cycle retention ≥95% after 500 cycles.

[0014] Thirdly, a positive electrode sheet is provided, comprising the lithium iron phosphate positive electrode material described in the second aspect of the present invention.

[0015] Fourthly, a lithium-ion battery is provided, comprising the positive electrode sheet described in the third aspect of the present invention.

[0016] Compared with existing technologies, this solution has the following advantages: (i) Avoid gradation failure caused by secondary sintering and accurately maintain the preset particle size peak shape. Existing technologies involve mixing separately crystallized primary particles and then subjecting them to a second high-temperature sintering process. Small particles are prone to surface melting and interparticle coalescence at high temperatures, disrupting the pre-designed bimodal / multimodal gradation structure and risking a narrowing of the product particle size distribution back into a single distribution. This invention independently prepares the first and second powders through a complete process from sand milling and spray drying to segmented sintering and pulverization. Once both powders are finished products, they are then mixed to match particle size peak shapes, eliminating the need for a second sintering process. This process design fundamentally avoids the destruction of the pre-designed gradation structure caused by the second high-temperature treatment, ensuring that the particle size distribution curve of the mixed powder accurately reflects the expected multimodal characteristics. The particle size distribution ratio is highly consistent with the design target, significantly improving the packing efficiency.

[0017] (ii) Unifying the source of precursors significantly improves process compatibility and batch stability. In existing technologies, different precursors are used for different particle sizes. The iron-phosphorus ratio, reactivity, and sintering behavior of these two precursors are inconsistent, requiring separate matching of process windows, which increases the complexity of raw material management, process control, and quality traceability. This invention uses the same ferrous phosphate precursor for both particle sizes, controlling the final powder particle size only by the difference in milling particle size. This raw material standardization allows both preparation processes to use the same equipment, differing only in process parameters. This facilitates parallel or alternating production on existing lithium iron phosphate production lines, significantly reducing process control difficulty and improving batch-to-batch consistency and product reproducibility.

[0018] (III) Introduce granularity distribution quantitative control parameters to achieve standardized design for peak shape matching. Existing technologies describe particle size distribution primarily through qualitative or empirical proportioning, lacking quantitative control indicators for the final product's particle size distribution characteristics. Significant differences in particle size distribution exist between different batches, making it difficult to meet the stringent reproducibility requirements of industrial production. This invention introduces a particle size distribution span parameter, Span = (D90...). The particle size distribution (D10) / D50 is controlled with a span of 2.5 ≤ Span ≤ 4.5 for the first powder and 2.0 ≤ Span ≤ 3.5 for the second powder. Peak shape matching ensures the particle size distribution curve of the mixed powder exhibits at least three peaks. This upgrades particle size distribution from an experience-based "trial-and-error" model to a quantifiable, repeatable, and traceable standardized process design, providing a quantitative control method for the large-scale, stable production of high-pressure lithium iron phosphate.

[0019] (iv) Simplify the carbon coating process and improve the accuracy of carbon content control. Existing technologies require the addition of carbon sources multiple times before the first sintering and during the second mixing, resulting in cumbersome process steps and a high risk of cumulative errors in carbon content. Too low a carbon content affects electronic conductivity, while too high a carbon content reduces compaction density and volumetric energy density. This invention adds the carbon source all at once during the precursor slurry preparation stage, eliminating the need for subsequent carbon replenishment. This simplifies process control points, reduces the risk of carbon content fluctuations, and makes precise control of the carbon content in the final product more reliable, achieving a balance between electronic conductivity and compaction density.

[0020] (v) No special additives are required, resulting in a simpler raw material system and lower costs. Existing technologies introduce C3N4 raw materials such as urea and melamine to improve conductivity, aiming to convert them into nitrogen-doped defective graphene through secondary sintering. However, the conversion efficiency and uniformity of C3N4 are greatly affected by fluctuations in sintering conditions, increasing the uncertainty of the process. This invention uses conventional carbon sources such as glucose and sucrose, achieving both high compaction and excellent electrochemical performance without relying on special additives. The raw materials are more readily available, procurement and control are simpler, and the process is more robust, which helps to reduce production costs and scale up production.

[0021] (vi) Synergistic improvement of high core density and excellent electrochemical performance The lithium iron phosphate material prepared by this invention has a compaction density of up to 2.50 g / cm³. 3 The above results are significantly superior to conventional processes. Furthermore, because each particle independently crystallizes under optimal sintering conditions, the carbon coating is complete and uniform, resulting in excellent electrochemical performance: a 0.1C discharge specific capacity ≥157mAh / g, and a capacity retention rate ≥95% after 500 cycles at 1C. This invention achieves high compaction density while simultaneously ensuring high discharge specific capacity and long-cycle stability, effectively overcoming the technical contradiction of "high compaction sacrificing electrochemical performance" in existing technologies. Attached Figure Description

[0022] Figure 1 The image shows a scanning electron microscope (SEM) image of the first powder prepared in Example 1 of this invention. Figure 2 This is a scanning electron microscope (SEM) image of the second powder prepared in Example 1 of the present invention; Figure 3 This is a particle size distribution curve of the lithium iron phosphate material prepared in Example 1 of the present invention. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] Example 1 (I) Preparation of the first powder (1) Weigh 100g of ferrous phosphate (Fe3(PO4)2·8H2O, purity ≥99.5%), add it to 300g of deionized water, add 24.74g of lithium phosphate (Li / Fe molar ratio of 1.05:1) as lithium source, 8.0g of glucose as carbon source, 0.3g of polyethylene glycol as dispersant, and 1g of titanium dioxide as titanium source, stir and mix evenly to obtain the first mixed slurry.

[0025] (2) The first mixed slurry was placed in a sand mill for sand milling for 1.5 hours, and the particle size D50 of the slurry after sand milling was controlled to be 0.30μm.

[0026] (3) The slurry after sand milling is spray dried and granulated. The spray drying inlet temperature is 220℃ and the outlet temperature is 105℃ to obtain the first precursor particles.

[0027] (4) The first precursor particles are placed in a tube furnace and sintered in stages under a nitrogen protective atmosphere: the first stage of sintering is carried out by heating to 400°C at 5°C / min and holding for 4 hours, and the second stage of sintering is carried out by heating to 700°C at 3°C / min and holding for 10 hours. The material is then naturally cooled to room temperature to obtain the first lithium iron phosphate sintered material.

[0028] (5) The first sintering material is subjected to air jet milling, and then classified by air jet classifier. The powder with concentrated particle size distribution is collected to obtain the first powder. The particle size of the first powder is measured as follows: D10=0.287μm, D50=0.852μm, D90=2.974μm, Span=3.153.

[0029] (II) Preparation of the second powder (6) Weigh 100g of ferrous phosphate (same batch as in step (1)), add it to 300g of deionized water, add 24.74g of lithium phosphate (Li / Fe molar ratio of 1.05:1) as lithium source, 8.0g of glucose as carbon source, 0.3g of polyethylene glycol as dispersant, and 1g of titanium dioxide as titanium source, stir and mix evenly to obtain the second mixed slurry.

[0030] (7) The second mixed slurry was placed in a sand mill for sand milling for 0.8 hours, and the particle size D50 of the slurry after sand milling was controlled to be 1.10 μm.

[0031] (8) Spray dry the slurry after sand milling to granulate it. The spray drying conditions are the same as in step (3) to obtain the second precursor particles.

[0032] (9) The second precursor particles are placed in a tube furnace and sintered in stages under a nitrogen protective atmosphere: the first stage of sintering is carried out by heating to 400°C at 5°C / min and holding for 4 hours, and the second stage of sintering is carried out by heating to 750°C at 3°C / min and holding for 10 hours. The material is then naturally cooled to room temperature to obtain the second lithium iron phosphate sintered material.

[0033] (10) The second sintering material is subjected to air jet milling, and then classified by air classifier. The powder with concentrated particle size distribution is collected to obtain the second powder. The particle size of the second powder is measured as follows: D10=1.204μm, D50=3.256μm, D90=9.744μm, Span=2.623.

[0034] (III) Particle size peak shape matching (11) The first powder and the second powder are mixed at a mass ratio of 50:50 and mixed in a high-speed mixer for 30 minutes to obtain high-pressure lithium iron phosphate material. Figure 3 The graph shows the particle size distribution of lithium iron phosphate material. The horizontal axis represents particle size (μm), and the vertical axis represents volume percentage (%). The curve exhibits a typical three-peak distribution characteristic.

[0035] Example 2 The difference between this embodiment and Embodiment 1 is as follows: The carbon source is sucrose, and the dispersant dosage is 0.4g; the first powder has a grinding particle size D50 of 0.35μm, and the second powder has a grinding particle size D50 of 1.30μm; the segmented sintering regime is: the first powder is pre-sintered at 450℃ / 3h and then sintered at 730℃ / 8h, the second powder is pre-sintered at 450℃ / 3h and then sintered at 750℃ / 8h; the peak shape matching mass ratio is 40:60. Details are as follows: (I) Preparation of the first powder (1) Weigh 100g of ferrous phosphate (Fe3(PO4)2·8H2O), add it to 300g of deionized water, add 24.74g of lithium phosphate (Li / Fe molar ratio of 1.05:1), 8.0g of sucrose as carbon source, 0.4g of polyethylene glycol as dispersant, and 1g of titanium dioxide as titanium source, stir and mix evenly to obtain the first mixed slurry.

[0036] (2) The first mixed slurry was placed in a sand mill for sand milling for 2 hours, and the particle size D50 of the slurry after sand milling was controlled to be 0.35μm.

[0037] (3) Spray drying granulation, under the same conditions as step (3) in Example 1.

[0038] (4) Segmented sintering: the first segment is sintered at 450℃ and held for 3 hours, and the second segment is sintered at 730℃ and held for 8 hours.

[0039] (5) After crushing and grading, the first powder is obtained with D10=0.312μm, D50=0.951μm, D90=3.157μm, and Span=2.992.

[0040] (II) Preparation of the second powder (6) Weigh 100g of ferrous phosphate, add it to 300g of deionized water, add 24.74g of lithium phosphate (Li / Fe molar ratio of 1.05:1), 8.0g of sucrose as carbon source, 0.4g of polyethylene glycol as dispersant, and 1g of titanium dioxide as titanium source. Stir and mix evenly to obtain the second mixed slurry.

[0041] (7) The second mixed slurry is placed in a sand mill for sand milling, and the particle size D50 of the slurry after sand milling is controlled to be 1.30μm.

[0042] (8) Spray drying granulation, under the same conditions as step (3) in Example 1.

[0043] (9) Segmented sintering: the first segment is sintered at 450℃ and held for 3 hours, and the second segment is sintered at 750℃ and held for 8 hours.

[0044] (10) After crushing and classifying, the second powder is obtained with D10=0.365μm, D50=3.801μm, D90=10.334μm, and Span=2.623.

[0045] (III) Particle size peak shape matching (11) The first powder and the second powder are mixed at a mass ratio of 40:60 to obtain high-pressure lithium iron phosphate material.

[0046] Example 3 The difference from Example 1 is that the mass ratio of the first powder to the second powder is 60:40.

[0047] Example 4 The difference between this embodiment and Embodiment 1 lies in the segmented sintering process: (1) The sintering process of the first powder is as follows: the first sintering is sintered at 300℃ and held for 2 hours, and the second sintering is sintered at 650℃ and held for 6 hours.

[0048] (2) The sintering process of the second powder is as follows: the first sintering is sintered at 300℃ and held for 2 hours, and the second sintering is sintered at 650℃ and held for 6 hours.

[0049] The other raw material types, dosages, grinding particle size, spray drying conditions, pulverization and grading conditions, and peak shape matching ratios are the same as in Example 1.

[0050] According to the laser particle size analyzer, the particle size of the first powder is: D10=0.298μm, D50=0.861μm, D90=2.985μm, Span=3.122; the particle size of the second powder is: D10=1.215μm, D50=3.268μm, D90=9.758μm, Span=2.614.

[0051] Example 5 The difference between this embodiment and Embodiment 1 lies in the segmented sintering process: (1) The sintering process of the first powder is as follows: the first sintering is sintered at 500℃ for 6 hours and the main sintering is sintered at 800℃ for 12 hours.

[0052] (2) The sintering process of the second powder is as follows: the first sintering is sintered at 500℃ for 6 hours and the main sintering is sintered at 800℃ for 12 hours.

[0053] The other raw material types, dosages, grinding particle size, spray drying conditions, pulverization and grading conditions, and peak shape matching ratios are the same as in Example 1.

[0054] The particle size distribution of the first powder, as measured by a laser particle size analyzer, is as follows: D10 = 0.275 μm, D50 = 0.840 μm, D90 = 2.952 μm, Span = 3.187; the particle size distribution of the second powder is as follows: D10 = 1.198 μm, D50 = 3.242 μm, D90 = 9.712 μm, Span = 2.626.

[0055] Example 6 The difference between this embodiment and Embodiment 1 is that: (1) The amount of lithium source was adjusted to a Li / Fe molar ratio of 1.01:1 (the amount of lithium phosphate added was 23.80g).

[0056] (2) The amount of dispersant polyethylene glycol added is adjusted to 0.1g (i.e. 0.1% of the mass of ferrous phosphate).

[0057] The other carbon source types and amounts, grinding particle size, spray drying conditions, segmented sintering regime, pulverization and grading conditions, and peak shape matching ratios are all the same as in Example 1.

[0058] The particle size distribution of the first powder, as measured by a laser particle size analyzer, is as follows: D10 = 0.282 μm, D50 = 0.848 μm, D90 = 2.965 μm, Span = 3.164; the particle size distribution of the second powder is as follows: D10 = 1.208 μm, D50 = 3.260 μm, D90 = 9.738 μm, Span = 2.617.

[0059] Example 7 The difference between this embodiment and Embodiment 1 is that: (1) The amount of dispersant polyethylene glycol added is adjusted to 1.0g (i.e. 1.0% of the mass of ferrous phosphate).

[0060] The other carbon source types and amounts, grinding particle size, spray drying conditions, segmented sintering regime, pulverization and grading conditions, and peak shape matching ratios are all the same as in Example 1.

[0061] The particle sizes of the first powder, as measured by a laser particle size analyzer, are as follows: D10 = 0.292 μm, D50 = 0.858 μm, D90 = 2.978 μm, Span = 3.131; the particle sizes of the second powder are as follows: D10 = 1.210 μm, D50 = 3.262 μm, D90 = 9.748 μm, Span = 2.618.

[0062] Example 8 The difference between this embodiment and Embodiment 1 is that the amount of carbon source (glucose) added is adjusted to 15.0g, so that the mass percentage of carbon in the final product is about 2.0%.

[0063] The other lithium source types and amounts, dispersant types and amounts, grinding particle size, spray drying conditions, segmented sintering regime, pulverization and classification conditions, and peak shape matching ratios are all the same as in Example 1.

[0064] The particle size distribution of the first powder, as measured by a laser particle size analyzer, is as follows: D10 = 0.278 μm, D50 = 0.845 μm, D90 = 2.958 μm, Span = 3.172; the particle size distribution of the second powder is as follows: D10 = 1.202 μm, D50 = 3.250 μm, D90 = 9.730 μm, Span = 2.624.

[0065] Comparative Example 1 Lithium iron phosphate powder with a single particle size distribution is used, without particle size peak shape matching.

[0066] The specific preparation steps are the same as steps (1) to (5) of Example 1, but the grinding particle size is controlled to be intermediate particle size (D50=0.55μm), and the preparation of the second powder and peak shape matching are not carried out. The sintered and pulverized powder is directly used as the final product.

[0067] The particle size of the final product was measured to be: D10 = 0.952 μm, D50 = 2.154 μm, D90 = 4.301 μm, and Span = 1.55. The particle size distribution curve exhibited a unimodal characteristic. No particle size peak shape matching was performed; the product was used solely for comparison as a single particle size sample.

[0068] Comparative Example 2 This comparative example is used to demonstrate the superiority of the present invention's "preparing the finished products separately and then mixing them without secondary sintering" over the prior art's "mixing and then secondary sintering".

[0069] The difference from Example 1 is that the first powder and the second powder prepared in Example 1 are mixed at a mass ratio of 50:50 and are not directly used as the final product. Instead, deionized water is added again to make a slurry (solid content 40%). After spray drying (inlet air temperature 210°C, outlet air temperature 105°C), the mixture is placed in a tube furnace and sintered at 770°C for 8 hours under a nitrogen protective atmosphere. Finally, the final product is obtained by air jet pulverization.

[0070] Comparative Example 3 This comparative example is used to demonstrate the necessity of quantitative control of the first powder's Span parameter for achieving effective gradation.

[0071] The difference from Example 1 is that the crushing and grading conditions of the first powder are different. By adjusting the grading parameters of the air classifier, the Span of the first powder is made to be less than 2.5.

[0072] The particle size of the first powder, as measured by a laser particle size analyzer, was: D10 = 0.452 μm, D50 = 0.887 μm, D90 = 1.596 μm, Span = 1.290. The preparation and peak shape matching conditions of the second powder were the same as in Example 1.

[0073] Comparative Example 4 This comparative example is used to demonstrate the necessity of controlling the Span parameter of the second powder.

[0074] The difference from Example 1 is that the crushing and classification conditions of the second powder are different. By adjusting the classification parameters of the air classifier, the Span of the second powder is greater than 3.5.

[0075] The particle size of the second powder, as measured by a laser particle size analyzer, was: D10 = 0.589 μm, D50 = 3.524 μm, D90 = 13.392 μm, Span = 3.633. The preparation and peak shape matching conditions of the first powder were the same as in Example 1.

[0076] Comparative Example 5 The difference from Example 1 is that the peak shape matching mass ratio of the first powder to the second powder is 90:10.

[0077] Performance testing The lithium iron phosphate materials prepared in the above embodiments and comparative examples were subjected to the following performance tests: (1) Particle size distribution test: The particle size distribution of the powder sample was tested using a laser particle size analyzer (Malvin 3000), and D10, D50, D90 and Span were calculated.

[0078] (2) Compacted density test: Take a certain mass of powder sample, put it into a mold, and press it into shape under constant pressure. Calculate the compacted density based on the mass and volume. The test pressure is 30 MPa, and the holding time is 30 seconds.

[0079] (3) Electrochemical performance testing: Lithium iron phosphate material was mixed with conductive carbon black and PVDF at a mass ratio of 90:5:5, NMP solvent was added to prepare the slurry, and the mixture was coated onto aluminum foil. After drying, rolling, and stamping, a positive electrode sheet was obtained. Using the lithium sheet as the counter electrode, 1 mol / L LiPF6 / EC+DMC+DEC (volume ratio 1:1:1) as the electrolyte, and Celgard 2400 as the separator, CR2032 coin cells were assembled in an argon glove box. Charge-discharge tests were performed on the Blue Battery testing system, with a voltage range of 2.0~4.2V.

[0080] The test results are shown in Table 1 below: Table 1 Test Results

[0081] Results analysis: (1) Analysis of results of Examples 1-8 As shown in Table 1, the particle size distribution curves of the lithium iron phosphate materials prepared in Examples 1-8 all exhibit a distinct three-peak characteristic, and the compaction density all reaches 2.54 g / cm³. 3 The above, up to 2.65 g / cm³ 3 The specific capacity at 0.1C discharge is ≥157.0mAh / g, the specific capacity at 1C discharge is ≥146.8mAh / g, and the capacity retention rate after 500 cycles at 1C is ≥95.5%.

[0082] Example 4 verified the lower limit combination of segmented sintering temperatures (300℃ / 2h for the first segment and 650℃ / 6h for the second segment). Under these temperature conditions, the sintering driving force is relatively weak, and particle growth is relatively slow, but the particles in each segment can still complete the basic crystallization process, with a compaction density of 2.56 g / cm³. 3 Although the performance is slightly lower than that of Example 1, it is still significantly better than the comparative examples. This demonstrates that the lower limit of the temperature range defined in claim 5 of the present invention has a reasonable technical effect.

[0083] Example 5 verified the upper limit combination of segmented sintering temperatures (500℃ / 6h for the first segment and 800℃ / 12h for the second segment). Under these temperature conditions, particle growth was relatively sufficient, and the compaction density reached 2.57 g / cm³. 3 However, excessively high sintering temperatures may lead to abnormal growth of a small number of grains, slightly reducing the uniformity of the grain size distribution. Overall, the upper limit combination still achieves a three-peak gradation and good electrochemical performance, demonstrating that the temperature range defined in claim 5 has reasonable technical effects.

[0084] Example 6 verified the combination of the lower limit of the lithium-iron ratio (1.01:1) and the lower limit of the dispersant dosage (0.1%), and Example 7 verified the combination of the upper limit of the dispersant dosage (1.0%). The results showed that, under the end values ​​specified in the claims, the product performance was still significantly better than that of the comparative examples. Example 8 verified the combination of the upper limit of carbon content (2.0%). The slightly higher carbon content resulted in a slight decrease in compaction density (2.54 g / cm³). 3 However, it is still better than each pair of proportions, proving the feasibility of the endpoint values ​​of the carbon content range.

[0085] Based on the results of Examples 4-8, all examples can achieve a three-peaked particle size distribution characteristic and a compaction density ≥2.54 g / cm³ under the conditions of the endpoint values ​​of each parameter defined in the claims. 3 The results are significantly better than those of the comparative examples, demonstrating that the numerical ranges defined in the claims of this invention have reasonable technical effects and can be fully supported by the specification.

[0086] (2) Comparison of Example 1 and Comparative Example 1 The compacted density of Example 1 was 2.65 g / cm³. 3 The concentration was significantly higher than that of control example 1 (2.43 g / cm³). 3 The improvement was approximately 9.1%. The particle size distribution of Comparative Example 1 exhibited a unimodal characteristic, with uniform particle size and a large number of voids when packed together; while Example 1, through the matching of the particle size peaks of the first powder and the second powder, formed a multi-level particle packing structure, effectively reducing the porosity between powders.

[0087] (3) Comparison of Example 1 and Comparative Example 2 Comparative Example 2 simulated the existing "mixing followed by secondary sintering" process. Its compacted density was 2.48 g / cm³. 3 Both the 1C discharge specific capacity (144.5 mAh / g) and the 2C discharge specific capacity were significantly lower than those of Example 1. The reason for this is that the secondary high-temperature sintering caused particle fusion and sintering adhesion between the separately crystallized first and second powders, disrupting the pre-designed multi-peak gradation structure and narrowing the particle size distribution. This demonstrates the significant advantages of the process design of this invention, which involves "preparing the powders separately and then mixing them, without the need for secondary sintering."

[0088] (4) Comparison of Example 1 and Comparative Example 3 In Comparative Example 3, the Span of the first powder was 1.290 (<2.5), and its particle size distribution curve after mixing with the second powder showed obvious "peaks and valleys," failing to form a smooth three-peak distribution. Its compacted density (2.46 g / cm³) was... 3 The concentration was significantly lower than that in Example 1 (2.65 g / cm³). 3 This indicates that when the span of the first powder is too narrow, the particle size is too concentrated, and there is a lack of sufficient fine and medium-sized particles to effectively fill the gaps between the particles of the second powder. This proves that the limitation of the lower limit of the span of the first powder (2.5≤Span) in this invention has important technical significance.

[0089] (5) Comparison of Example 1 and Comparative Example 4 In Comparative Example 4, the Span of the second powder was 3.633 (>3.5). Although its D50 was similar to that of Example 1 (3.524 μm vs 3.256 μm), the particle size distribution was too wide and the fine powder content was too high after mixing with the first powder, resulting in an increased specific surface area and affecting the particle packing efficiency and electrochemical performance. Its compacted density (2.45 g / cm³) was... 3 Both the 1C discharge specific capacity (144.2 mAh / g) and the 1C discharge specific capacity are lower than those of Example 1, indicating that when the span of the second powder is too wide, excessive fine powder interferes with the establishment of an effective gradation. This proves that the limitation of the upper limit of the span of the second powder (Span≤3.5) in this invention has important technical significance.

[0090] (6) Comparison of Example 1 and Comparative Example 5 In Comparative Example 5, the mixing ratio of the first powder to the second powder was 90:10, and its compacted density was 2.41 g / cm³. 3 The value was the lowest among all samples. The reason is that when there are too many small particles and not enough large particles, there is a lack of sufficient skeleton particles to support the particles, and the small particles cannot form an effective gradation structure by themselves.

[0091] The above descriptions are merely embodiments of the present invention, and common knowledge regarding specific structures and characteristics is not elaborated upon here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the structure of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor, characterized in that: Includes the following steps: S1. Preparation of the first powder: Ferrous phosphate precursor, lithium source, carbon source, titanium source, dispersant and solvent are mixed to obtain a first mixed slurry; then the first mixed slurry is sand-milled to obtain a first sand-milled slurry; the first sand-milled slurry is spray-dried and granulated, and the resulting material is then subjected to segmented sintering, crushing and classification to obtain the first powder; wherein, the particle size D50 of the first sand-milled slurry is 0.2~0.4μm; the D50 of the first powder is 0.6~1.2μm, and the particle size distribution span is 2.5~4.5; the segmented sintering is carried out in two stages under a protective atmosphere, the first stage sintering temperature is 300~500℃, and the second stage sintering temperature is 650~800℃; S2. Preparation of the second powder: Ferrous phosphate precursor, lithium source, carbon source, titanium source, dispersant, and solvent are mixed to obtain a second mixed slurry; then the second mixed slurry is milled to obtain a second milled slurry; the second milled slurry is spray-dried and granulated, and the resulting material is then subjected to segmented sintering, pulverization, and classification to obtain the second powder; wherein, the particle size D50 of the second milled slurry is 0.8~1.5μm; the D50 of the second powder is 2.5~4.5μm, and the particle size distribution span is 2.0~3.5; the segmented sintering is carried out in two stages under a protective atmosphere, with the first stage sintering temperature at 300~500℃ and the second stage sintering temperature at 650~800℃; S3. Peak shape matching: The first powder and the second powder are mixed so that the particle size distribution curve of the mixed powder exhibits at least three peaks, thereby obtaining high-pressure lithium iron phosphate material.

2. The process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor according to claim 1, characterized in that: In both S1 and S2, a sand mill is used for sand grinding, and the grinding time is 0.5 to 3 hours.

3. The process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor according to claim 1, characterized in that: In S1 and S2, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate; the carbon source is selected from at least one of glucose, sucrose, polyethylene glycol, citric acid, and carbon nanotubes; the titanium source is selected from at least one of titanium dioxide, titanium oxysulfate, chelated titanium, and metatitanic acid; the solvent is deionized water; and the dispersant is selected from one or more of ammonium polyacrylate, polyethylene glycol, and polyvinylpyrrolidone.

4. The process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor according to claim 1, characterized in that: In S1 and S2, the amount of dispersant added is 0.1% to 1.0% of the mass of the ferrous phosphate precursor in each step; the molar ratio of lithium to iron in the lithium source and the ferrous phosphate precursor in each step is 1.01:1 to 1.05:1; the amount of titanium source added in each step is 0.4% to 1.5% of the mass of the ferrous phosphate precursor in each step; and the amount of carbon source added in each step is such that the mass percentage of carbon in the powders prepared in S1 and S2 is 1.0% to 2.0%.

5. The process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor according to claim 1, characterized in that: In S1 and S2, the first stage sintering is followed by heat preservation for 2 to 6 hours, and the second stage sintering is followed by heat preservation for 6 to 12 hours. In each step, the pulverization is mechanical pulverization and / or airflow pulverization, and the grading is performed using an airflow classifier or a vibrating screen.

6. The process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor according to claim 1, characterized in that: The protective atmosphere is nitrogen or argon.

7. The process for preparing high-pressure lithium iron phosphate based on ferrous phosphate precursor according to claim 1, characterized in that: In S3, the mass ratio of the first powder to the second powder is 30:70 to 70:

30.

8. A lithium iron phosphate cathode material, characterized in that: The lithium iron phosphate cathode material prepared by the process described in any one of claims 1-7 has a compaction density ≥ 2.50 g / cm³. 3 0.1C specific capacity ≥157mAh / g, 1C cycle retention ≥95% after 500 cycles.

9. A positive electrode plate, characterized in that: It includes the lithium iron phosphate cathode material as described in claim 8.

10. A lithium-ion battery, characterized in that: It includes the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • High-compaction lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN120039852A

  • Lithium iron phosphate powder and preparation method thereof

    CN120246971A

  • Preparation method of lithium iron phosphate positive electrode material

    CN120887394A

  • Lithium iron phosphate material, preparation method thereof and lithium ion battery

    CN121085239A

  • High-compaction and high-rate lithium iron phosphate synthesized from ferrous phosphate and preparation method of high-compaction and high-rate lithium iron phosphate

    CN121225563A